Pengaruh Pengeluaran Pemerintah Bidang Pendidikan, Gender Gap dan Pendapatan Per Kapita Terhadap Ketimpangan Pendidikan dan Ketimpangan Pendapatan Kabupaten/Kota di Provinsi Kalimantan Barat - Hamzah, Fahrur; Rosyadi, Rosyadi; Kartika, Metasari (Fakultas Ekonomi dan Bisnis, UNTAN, 2017)
This study aims to analyze the impact of government expenditures, gender gap and per capita income on the education and income inequalities of regencies and cities in West Kalimantan Province. This research used secondary data in a form of data panel. These data include time series data for 5 years (2011